(untitled) (Revista Argentina de Musicología, 2018)
Historically, the association between social movements and musical practices that represent them is so consistent, that seems impossible break it. Nevertheless, the pan-Indian Argentine movement could become an example of it. Not because musical expressions do not occur in the "meetings" but due to the regional diversity of these practices. This is the central subject. Previously, I offer the case of American pan-Indianism as a contrasting example, an outline of aboriginal visibility and invisibility in Argentina through history, and a synthesis of the rise of Argentine movement. I conclude with a reflection on the suitability of certain non-indigenous musical practices to represent the movement in the future, and on the paradoxical sense of this potential fact.